How does the social context fuel the proactive fire? A multilevel review and theoretical synthesis - Cai, Zijun; Parker, Sharon K.; Chen, Zhijun; Lam, Wing (Journal of organizational behavior, 2019)
The role of social context (e.g., leadership, team climate, and organizational support) in shaping employee proactive behavior has received considerable attention and has been investigated across multiple forms of proactive behavior. However, the research has not been well integrated. In this review, we adopt a multilevel approach to synthesize what is known about how social context factors influence employees’ proactive behavior, as well as what mechanisms underpin these effects. Our analyses show that leader-, team-, and organization-related social context factors mainly influence employee proactivity through shaping “reason to,” “can do,” and “energized to” states (i.e., proactive motivational states) via individual-, team-, and cross-level processes. That has been most frequently investigated is the effect of the discretionary social context, particularly leadership, on proactive behavior. We also review the interaction effects between social context factors and other factors on employee proactive behavior and found inconsistent support for the motivational-fit perspective that stimuli with the same directions enhance each other’s effect. We offer a research agenda to advance theoretical insights on this important topic.